Hilbert Transform Based Adaptive ECG R-Peak Detection Technique - Nikunj Makwana; Nikunj Hasmukhbhai Makwana; Nishant Mishra; Balwalli Sagar (Institute of Advanced Engineering and Science, 2012)
In this paper we introduce a R-peak detection algorithm using the Hilbert transform for electrocardiogram processing. This algorithm uses the envelope obtained from Hilbert transform to detect the R-peaks in the ECG signal. The algorithm adaptively determines the threshold for peak determination. This technique minimizes the unwanted effects of large peaked T and P waves. Main advantage of this algorithm is that it performs extremely well in the pragmatic presence of noise.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1439